Analgesic Effect of Low-Level Laser Therapy before Heel Lance for Pain Management in Healthy Term Neonates: A Randomized Controlled Trial - Bei-Yu Wu; Mei-C; Chun-Ting Liu; Hsin-Chun Huang; Wen-Long Hu; I-Lun Chen; Hsin-Yu Chang; Mei-Yung Chung; Feng-Shun Chen; Yung-Hsiang Chen; Chih-Cheng Chen (MDPI AG, 2023)
Currently, the prevention, assessment, and management of procedural pain in neonates continues to challenge clinicians and researchers. Objective. To investigate the analgesic effect of low-level laser therapy (LLLT) during heel lance compared to breast milk (BM) feeding in healthy term neonates. In this randomized controlled trial, healthy term neonates who underwent heel lance were randomly assigned to an LLLT or a BM group. The LLLT group received laser therapy to the heel lance site for 20 s before heel lance. The BM group received 5 mL expressed BM via a syringe before heel lance. The primary outcomes were behavioral responses. The secondary outcomes were physiological responses and levels of salivary cortisol and α-amylase. A total of 125 neonates were included, of whom 55 in the LLLT group and 59 in the BM group completed the study. There were no significant differences in latency to first cry and cry duration between the two groups. The squeeze time was significantly shorter in the LLLT group than in the BM group (p = 0.047). There were no significant differences in pain scores, heart rate, respiratory rate, oxygen saturation, and blood pressure before and after heel lance between the two groups. There were no significant differences in salivary cortisol and α-amylase levels in the LLLT group before and after heel lance; however, the differences were significant in the BM group. These findings suggest that the analgesic effect of LLLT is similar to that of BM during heel lance in healthy term neonates. LLLT has potential as an analgesic treatment.